AKUNTANSI BERBASIS TEENLIT SEBAGAI UPAYA PENINGKATAN MINAT BACA DAN MOTIVASI PEMBELAJARAN AKUNTANSI DASAR - Romi Kurniadi; Wira Aditya; Devi Reza (Jurnal Pendidikan, 2022)
This study aims to develop teenlit-based accounting teaching materials on basic accounting learning materials as an effort to overcome the problem of students' low interest in reading, especially in learning books. This development research using the Hanafin and Peck method. The development in this research goes through the stages of needs analysis, design, and development. The results of the study show that the needs that are the main priority for product development are in the form of supplementary reading materials for students who present accounting lessons with interesting storytelling methods, current diction, and brief and simple explanations of learning materials. Product design goes through six processes including (a) determining the problem/topic of the story, (b) choosing the way of opening/leading, (c) determining the setting of the story, (d) characters and characterizations, (e) storyline, and (f) learning content. Product development focuses on strategies in the form of (a) interesting openings, (b) youth world atmosphere, (c) pithy conversations, (d) simulations, and (e) exercises, instructions, and answer keys.